Sin Taxes, Insurance and the Correction of Internalities - Zarko Kalamov; Marco Runkel (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We analyze individuals with heterogeneous time-inconsistent preferences that consume sin goods and make a savings decision. A government may tax the sin good and provide mandatory health insurance. Due to time-inconsistency, the individual sin good and savings choices in ict internalities. Due to the ex-ante moral hazard of health insurance, sin good consumption also causes an externality. If the individuals' utility is such that savings and sin good demand decisions are decou- pled, the government can achieve the first-best outcome using a uniform tax rate and uniform health insurance. Moreover, in the optimum, the tax rate internalizes only the externality and the government provides full insurance. When the savings and sin good consumption choices are interrelated, the government can still achieve the first-best outcome by additionally using Social Security to stipulate minimum savings requirements.
Keywords: D11; D15; H21; H31; I12; I13; I18; 330; sin tax; health insurance; moral hazard; hyperbolic discounting; internality